2022
DOI: 10.1007/s42600-022-00253-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of heart disease using oversampling methods and decision tree classifier in cardiology

Abstract: Purpose Heart disease is one of the most prevalent and critical diseases that endangers the lives of human beings. In addition to clinical diagnosis, machine learning and deep learning-based approaches are vital in the diagnosis of heart disease. Method This paper proposes a balanced and optimized machine-learning algorithm for heart disease detection. This technique combines oversampling techniques, attribute pruning, CART decision tree classifier, and rule pruning thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Hence, the process of generating new data is very much typical in healthcare applications. Albert et al [12] recently used smote and adasyn approach to detect heart disease using ML algorithms. The result has shown that oversampling improved model performance by 11% compared to the original dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, the process of generating new data is very much typical in healthcare applications. Albert et al [12] recently used smote and adasyn approach to detect heart disease using ML algorithms. The result has shown that oversampling improved model performance by 11% compared to the original dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penyakit jantung merupakan salah satu penyakit paling umum dan kritis yang membahayakan kehidupan manusia. Selain diagnosis klinis, pembelajaran mesin dan pendekatan berbasis pembelajaran mendalam sangat penting dalam diagnosis penyakit jantung [7].…”
Section: Pendahuluanunclassified